Marketing Plan For Boosting Sales - Fitriyah Astri; Heny Herawati; Seska Gampu; Nita L. Ssalam; Betty Rahayu (Jurnal Mirai Management, 2023)
The purpose of this study is to learn more about marketing tactics used to boost sales at CoffeePurnama. The research approach is a sort of qualitative inquiry that makes use of descriptive qualitative methods. This study directly observes important informants and informants through observations, interviews, documentation, and focus group discussions (FGDs). The findings of this study suggest that Coffee Purnama's marketing strategy is sound because Purnama Coffeee has the advantages and potential to compete with its rivals in the market today. One such opportunity is to develop product innovations. On the down side, though, the full moon Coffeee also contains risks and flaws that could cause it to fail. Purnama Coffeee's threats and weaknesses are inconsistent open sticks, poor promotions, and insufficient locations. This danger served as a catalyst for CoffeePurnama to increase the next aim. According to the current plan, it is most effective to keep promoting CoffeePurnamayang in areas where this strategy can make the most of its advantages and opportunities. Keywoard: Marketing Strategy; Sales